Improving Character Education In The Learning And Learning Process Of SMAN 13 GOWA Students - Hajrah, Hajrah; Prayogi, Ivan; Nuratika, Nuratika; Awaru, A. Octamaya Tenri (Jurnal Pendidikan Indonesia, 2024)
Improving character education is a key to forming positive habits so that children can act and behave in accordance with the values that have become their personality, therefore there is definitely room for improvement. In this case, character education needs to be taught regularly and developed until it is ingrained in students. This research is motivated by observation data which shows an increase in character education in the teaching and learning process of SMAN 13 GOWA students. Improving character education is important for children, adults and society. People's understanding of the world around them increases thanks to education. Additionally, it helps improve communication and expression of opinions. This aims to encourage the development of the individual's overall personality. Forming an individual's character and attitude towards other people's lives becomes a learning experience where a person learns various aspects of life, understands various points of view, and tries to apply them in everyday life can play an important role in education.